Anti-arthritic activity of Alternanthera paronychioides through suppression of inflammatory cytokines and NF-κB signaling (Bangladesh Journal of Pharmacology, 2026)
Alternanthera paronychioides is traditionally used for managing inflammatory disorders; however, its anti-arthritic efficacy and underlying mechanisms remain insufficiently characterized. The present study evaluated the anti-arthritic potential of A. paronychioides in acute and chronic animal models of arthritis. Previously, sequential extracts were assessed for inhibition of protein denaturation, proteinase activity, and erythrocyte membrane destabilization. The most active n-hexane extract was further investigated in carrageenan-induced inflammation and complete Freund’s adjuvant-induced arthritis in rats. n-Hexane extract treatment significantly reduced paw edema, arthritic severity, hyperalgesia, and allodynia, while improving histopathological, and radiographic outcomes. Molecular analysis revealed marked suppression of pro-inflammatory mediators, including TNF-α, IL-1β, IL-6, NF-κB, and COX-2, alongside up-regulation of IL-4. These findings demonstrate that A. paronychioides exerts potent anti-arthritic effects through multi-target immunomodulation.